Chemistry of spices - Parthasarathy, Villupanoor A (Cabi, 2012)
Representing a discussion of the chemical properties of a cross section of spices, this book covers the three categories of plant-derived natural products: the terpenoids, the alkaloids and the phenyl propanoids and allied phenolic compounds. It covers spice crops such as black pepper, ginger, turmeric and coriander.